The use of L1 in L2 Learning in the Indonesian EFL context - Muqit, Abdul; Sahiruddin, Sahiruddin; mron, Aly; Nurhayati, Nurhayati; Polii, Intama Jemy (Universitas Muhammadiyah Sidoarjo, 2023)
The issue of L1 usage in the L2 classroom is still open. Historically, using the target language was the most effective method for learning L2. However, some research indicates that incorporating L1 into L2 sessions can also help to improve second language learning. The notion of L1 use is in the L2 classroom has also been associated with the notion of translanguaging in the bilingual or multilingual education. The goal of this study is to ascertain the attitudes and beliefs of teachers and students towards the use of first language in the second language classroom and to determine the extent to which such beliefs regarding the use of first language in the L2 classroom is related to one another to facilitate L2 learning. Participants in this study were 115 students (n=115) and 30 university English teachers (n = 30). A questionnaire was used to obtain the data, and descriptive statistics was employed. The study revealed that teachers and students are generally in favor of using L1 in L2 classrooms (bilingual instruction), depending on the context or goals. The L1 is used primarily to enhance L2 proficiency so that as the L2 proficiency progresses, monolingual approach can be implemented. This study partially supports the viability of a bilingual or co-taught method in the L2 classroom. HIGHLIGHTS: Teachers and students favor using a second language (bilingual approach) to facilitate learning inthe second classroom. For L2 learners to build their L2 skills, they need to be exposed to as much L2 input as possible.L2 learning and development heavily rely on the use of L1 to connect L1 and L2 information. Indonesian EFL classes can adopt the bilingual to monolingual EMI transition paradigm asreferring to students’ proficiency levels.